University students' perceptions of graduate employer selection tests - Martyn Quigley (Education + Training, 2024)
Purpose: The purpose of the current study was to examine university students' knowledge, confidence and experience of popular graduate employer selection tests. Design/methodology/approach: A cross-sectional self-report survey was administered to gather a sufficient number of quantitative responses from undergraduate students. A total of 241 students completed the survey with most of them being psychology students from Swansea University. Four key variables were examined: (1) students' experience, (2) confidence and (3) knowledge of selection tests and (4) their desire for more information about selection tests as part of their degree. An audit of selection tests used by the Times Top 100 graduate employers was also conducted. Findings: Students tended to misjudge how often selection tests were used by employers, and generally lacked experience with these tests. Students' confidence in completing each test varied as a function of the selection test; however, prior experience with these tests positively predicted confidence. Additionally, over 70% of students reported a desire for further information about selection tests as part of their degree. Practical implications: These novel findings suggest that students could benefit from further information about selection tests as part of their degree programme which would be of benefit to both students and universities. Originality/value: These findings are, to the authors knowledge, the first to explicitly assess second- and third-year undergraduate students' knowledge, experience and confidence with popular graduate employer selection tests and demonstrate that students would like more information about these tests on their programme.